The Use of YouTube videos to Improve Students' English Pronunciation Skills - Sulistiyaningsih, Riski (English Education Department - Universitas Nasional Karangturi, 2024)
English pronunciation is a language skill that must be mastered well by students studying English, especially in the teaching department. Pronunciation that is less than perfect will result in misunderstandings and the meaning of the vocabulary can also be different. During the learning process in the classroom, the way of how to pronounce vocabulary is only given by the lecturer, which sometimes makes the class atmosphere less varied and students become less active. Therefore, this research discusses the effectiveness of videos on YouTube which are used as learning media during the English learning process in the classroom. This research uses a qualitative descriptive method with data in the form of the average results of students’ scores in English pronunciation which are tested orally. The research results show that the use of YouTube videos is very effective in improving students' pronunciation skills because the videos displayed come from native speakers who use British and American accents. In other words, videos on YouTube can become one of effective English pronunciation learning media. The research results also showed an increase of student scores in English pronunciation and students were more enthusiastic during the learning process in the classroom.